Comparative Effects of Phyllantus Amarus on the Serum Electrolyte Level of Hypertensive and Normotensive Male Wistar Rats: Phyllantus Amarus on the Serum Electrolyte Level - Ifabunmi Osonuga; Bello Solape Faderera; Olukade Baliqis Adejoke; Ogunlade Albert Abiodun; Ezima Esther Nkechi; Adegbesan Bukunola Oluyemisi; Olalekan Samuel Oluwadare (Universitas Airlangga, 2023)
Highlights: It discusses effects of phyllantus amarus on serum electrolyte which results in an imbalance. The reducing effect oh sodium and chloride levels implicate a new chance in managing hypertension. Abstract: Background. High blood pressure, also known as hypertension, is one of the most well-known major risk factors for cardiovascular disease (CVD) and stroke. Aims. This present study tried to compare the effect of P.amarus leaves on normotensive and hypertensive male Wistar rats. Materials and method. 15 male Wistar rats were divided into three groups of five rats each (Control group, Control + Extract group, and Hypertensive+ Extract group). One of the groups of rats (group 3) was induced with hypertension using 0.5mg/kg for 5 days of Dexamethasone. Then, the normal/control group and the hypertensive were treated with 200mg/kg of aqueous Extract of Phyllantus amarus (AEPA) for 28 days. Fasting venous blood samples were collected for the measurements of serum electrolytes. Serum potassium, sodium, and chlorine levels were measured by the ion-selective electrode method. Results. In this experiment, for the normotensive and hypertensive treatment groups respectively, there was an increase in K⁺ level and decrease in K⁺ level compared to the control rats, decrease in Na⁺ level, and decrease in Na⁺ level. Also, a decrease in Clˉ of normotensive rats while there was no change in the Clˉ level of hypertensive group when compared to control group. The p values for all results were found to be non-significant. Phyllantus amarus has an effect on serum electrolyte imbalance. Its reducing effect on sodium and chloride levels implies that it can be used to manage hypertension, thereby reducing the risk of developing cardiovascular diseases.